SISTEM KENDALI POMPA AIR BERSIH PADA GEDUNG BERTINGKAT - Sugeng, Sugeng; Yusril, Yusril (JREC (Journal of Electrical and Electronics), 2014)
Water pump control system in buildings is a control system that is used to control the watersupply in buildings from ground water reservoir (GWR) to the top tanks at storey building.Water pump control system is equipped with some very important components for controllingand securing the pump control system. Water pump control system consist of several sensorssuch as water level sensor (radar switches), flow switches, overload and temperature sensorusing a thermostat.Switch radar is used to detect the volume of water in each tanks that tanks conditionsremain guaranteed availability. Switch radar that detects this state is in full tank or empty thusaffecting the work of filling the water pump.When the pump motor on, then the system will read the conditions of flow switch.Flow switches are used to detect the flow of the pump. When the pump is working but thereis no water then the timer will cut off contact when reaching the setting t + 0.33 seconds toturn off the pump motor. To protect the motor from overheating, the system is equipped witha temperature sensor using a thermostat that will cut off contact with the thermostatdisconnect the current contactor. Thermostat will cut off contact when the heat reaches anaverage of 62.74 Â° C and buzzer alarm will sound, Then be back in contact when the heatdown until average 41.14 Â°C. While the overload function to secure or provide protectionfrom damage caused by over loading on the motor.Keyword : switch radar, flow switch, thermostat, overload